THE QUALITY OF EDUCATION IN 50 COUNTRIES REVIEWED FROM SUSTAINABLE DEVELOPMENT GOALS: SYSTEMATIC LITERATURE REVIEW - Lubis, Alya Syafitri; Aryansah, Januar Eko (Natapraja, 2023)
Education is an essential aspect of a country. This research aimed to look at countries that implement good quality education and find out what the indicators of the country are in improving the quality of education for sustainable development or see which indicators are used the most in quality education. This research is a systematic literature review. Based on the PRISMA method that has been carried out, a total of 51 journal articles were used in the literature study, and they were obtained from Google Scholar, DOAJ, ScienceDirect, and PubMed. The research results show that indicators of quality education are measured by reliable teaching staff, lifelong education, and completeness of facilities and infrastructure. Of the 51 journal articles examined, 20 journal articles used the indicator of reliable teaching staff as an indicator of education quality, 17 journal articles used lifelong education as an indicator of education quality, and 22 journal articles used indicators of completeness of facilities and infrastructure. These results make completeness of facilities and infrastructure the key to success in creating quality education for sustainable development goals.